2022
DOI: 10.3390/polym14112171
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Polymer Blends of Poly(methyl methacrylate) and Poly(propylene glycol)

Abstract: Polymer blends, obtained by polymerization of methyl methacrylate in the presence of poly(propylene glycol), are investigated. Poly(propylene glycol) acts as a plasticizer, significantly lowering poly(methyl methacrylate)’s glass transition temperature and decreasing its elasticity modulus and yield stress. The mixture of methyl methacrylate with poly(propylene glycol) is more stable than its mixture with currently used poly(ethylene glycol), which leads to more uniform distribution and higher possible content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…This plot shows that the minimum value of color difference was obtained between initiator values 0.12 and 0.16 mg/100 mL GS as the plasticizer was increased. It indicates that the color difference increased with increasing the concentration of plasticizer and decreasing the concentration of initiator reason being the lesser number of free radicals released by the initiator and the film being more transparent due to the high concentration of the plasticizer [ 37 ]. Similarly, Figure 2(c) shows the contour plot between crosslinker and plasticizer concentration at the optimum point of the initiator (0.15 mg/100 mL GS).…”
Section: Resultsmentioning
confidence: 99%
“…This plot shows that the minimum value of color difference was obtained between initiator values 0.12 and 0.16 mg/100 mL GS as the plasticizer was increased. It indicates that the color difference increased with increasing the concentration of plasticizer and decreasing the concentration of initiator reason being the lesser number of free radicals released by the initiator and the film being more transparent due to the high concentration of the plasticizer [ 37 ]. Similarly, Figure 2(c) shows the contour plot between crosslinker and plasticizer concentration at the optimum point of the initiator (0.15 mg/100 mL GS).…”
Section: Resultsmentioning
confidence: 99%
“…Himeno et al [ 17 ] showed that collagen can reduce irritation because it decreases inflammation and also has a skin-remodeling function. PEG had a significant quadratic effect that increased the breaking strength because PEG, together with Kollicoat ® Protect, reduces the intermolecular forces of the polymer, increasing its mobility and allowing the polymer chains to move more freely, giving it greater flexibility and strength [ 18 ]. In terms of bioadhesion, PEG has a moisturizing effect that confers adhesive properties because the formation of hydrogen bridges allows better interaction between the formulations and the substrate, which in this case, is the skin [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 illustrates how the formulations generate hydration in the wounds for both diabetic and healthy rats compared to the control wound and healthy skin. This outcome is due to the D-panthenol and PEG that the formulations contain, which provide hydration to the tissue [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%